2014 Information Theory and Applications Workshop (ITA) 2014
DOI: 10.1109/ita.2014.6804238
|View full text |Cite
|
Sign up to set email alerts
|

High SNR capacity of millimeter wave MIMO systems with one-bit quantization

Abstract: Abstract-Millimeter wave (mmWave) is a viable technology for future cellular systems. With bandwidths on the order of a gigahertz, high-resolution analog-to-digital converters (ADCs) become a power consumption bottleneck. One solution is to employ very low resolution one-bit ADCs. This paper analyzes the flat fading multiple-input multiple-output (MIMO) channel with one-bit ADC. Bounds on the high signal-to-noise ratio (SNR) capacity are derived for the single-input multiple-output (SIMO) channel and the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 22 publications
1
84
0
1
Order By: Relevance
“…In [12], we considered the channel capacity of the flat-fading narrowband MIMO channel with 1-bit ADCs shown in Fig. 3.…”
Section: Capacity Analysis With 1-bit Adcs -Withmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12], we considered the channel capacity of the flat-fading narrowband MIMO channel with 1-bit ADCs shown in Fig. 3.…”
Section: Capacity Analysis With 1-bit Adcs -Withmentioning
confidence: 99%
“…5, we plot the upper bound of the mmWave channel capacity with 64 transmitter antennas [12]. The receiver antennas and the number of paths are both assumed to be no more than 16.…”
Section: Performance Comparisonsmentioning
confidence: 99%
“…The use of one-bit ADCs in massive MIMO, was initially studied in [15]. The use of onebit ADCs had previously also been studied for MIMO systems in, e.g., [16,17] and for millimeter wave MIMO systems in, e.g., [18]. The feasibility of one-bit ADCs, in terms of achievable rate, was studied in [17], where it was shown that one-bit ADCs only lead to a small capacity reduction in a MIMO system at high noise levels, and in [19], where it was shown that the capacity at low noise levels is very high and scales linearly with the number of receive antennas.…”
Section: Massive Mimomentioning
confidence: 99%
“…Such low bit resolution mmWave front-ends have been studied in [22], [23], [42]- [44]. In [44] specifically, the authors discuss among other things the impact of ADC resolution on the communication rate after the link has been established.…”
Section: Fully Digital Bf With Low Bit Resolutionmentioning
confidence: 99%